PENENTUAN STRATEGI PEMASARAN WARMINDO RIVERSIDE NUSUKAN MENGGUNAKAN ANALISIS SWOT - Nanda Nanda; Endang Winarsih; Ahmad Husin (JURNAL ILMIAH EDUNOMIKA, 2023)
The economic business of buying and selling is one of the businesses that supports the wheels of the economy and is also the most interested in the community. Large, densely populated cities are suitable land for business actors in the culinary sector. Micro, small and medium enterprises (MSMEs) are an important part of the economy of a region or country. Strategies based on the marketing mix include: (1) Product, namely creating product differentiation so that it is different from other similar products, maintaining and improving product quality and using appropriate and attractive packaging (2) Price, namely setting a product price that can be reached by consumers (3) Place, which has outlets with attractive packaging designs and concepts, has roadside locations and opens several branches in several other places (4) Promotion, namely conducting sales promotions through sales directly (personal selling), word of mouth (word of mouth) and using social media and using advertising services. Strategies based on segmentation, targeting, positioning (STP) include: (1) Segmentation, which is to group consumers based on demographics in terms of age, occupation, and income to differentiate the packaging and prices offered (2) Targeting, namely setting targets for people living in the area around the outlet, consumers who know from social media and open branches in other places to expand the target market (3) Positioning, namely how to create a tagline which is a typical saying of the city of Solo, namely "Warmindo Riverside, not canned Indomie culinary cuisine" , the tagline means that Warmindo Riverside is not an ordinary Indomie culinary dish, but a different Indomie culinary dish, in this case Warmindo Riverside must really show that its uniqueness is a positive and attractive thing for consumers.